Bearsuit Turtle plays a game - Shea, Bob (Abrams Books for Young Readers, 2026)
A turtle in a bearsuit and his friend play a seemingly rule-less game of bearsketball that gets increasingly off-the-walls as the friends avoid pretend lava, roll down hills, and search for the biggest stick to become the winner.